Respuesta :

199932

[tex](2x - 8)(2x + 9) \\ 4 {x}^{2} + 18x - 16x - 72 \\ 4 {x}^{2} + 2x - 72[/tex]

HOPE IT HELPS

PLEASE GIVE BRAINLIEST

Step-by-step explanation:      

Step 1: Simplify

[tex](2x -8)(2x+9)[/tex] - Equation

[tex]= (2x+-8)(2x+9)[/tex] - Simplify

[tex]=(2x)(2x)+(2x)(9)+(-8)(2x)+(-8)(9)[/tex] - Answer

[tex]= 4x^2+18x-16x-72[/tex] - Simplify again

[tex]=4x^2+2x-72[/tex] - Final Answer

Explanation in words (Short Form)

-  The first step is to use the formula and simplify it. So first we will Rewrite the division as a fraction.

- The second step is to simplify the equation that was provided. The equation is (2x-8)(2x+9). We will apply the FOIL Method (Math) to solve this equation. Here is the formula: [tex]\left(a+b\right)\left(c+d\right)=ac+ad+bc+bd[/tex]

Answer:  

[tex]=4x^2+2x-72[/tex]

Hope this helps.

ACCESS MORE